(untitled) (Journal of Tikapur Multiple Campus, 2017)
In this 21st Century teachers are pillar of the nation. They are playing greater roles and given bigger commitments in the profession. These increased responsibilities and higher expectations do take its toll on them. Job satisfaction is indeed most crucial not only in determining the faithfulness of an employee to an organization but more importantly it is the main indicator of an individual’s level of commitment and productivity in his or her profession. This study aims to investigate the job satisfaction among college teachers. The purposes of the study are to investigate the differences in job satisfaction among teachers with different years of teaching experience, to identify the relationship between years of teaching experience and job satisfaction, and to identify the differences between male and female teachers in job satisfaction. A quantitative approach which used a questionnaire, Modified form of Teacher Job Satisfaction Questionnaire’ (TJSQ) developed by Lester (1982), was used as the main instrument to evaluate job satisfaction among teachers in Community Campuses in Kailali district. 50 teachers became the respondents from three Campuses (TMC, LMC and GMC) of three municipalities for this research. It is concluded that there is no significant relationship between years of teaching experience and job satisfaction. There is no correlation between male and female teachers possessing respective faculties and designations in community campuses. Overall, this research indicates that the teachers in the college level are generally satisfied with their work.